"It's Hard to Show Empathy in a Text": Developing a Web-based Sexual Assault Hotline in a College Setting. Issue 17 (September 2022) - Moylan, Carrie A.; Carlson, Melanie L.; Campbell, Rebecca; Fedewa, Tana
To increase access to counseling and advocacy services and respond to changes in communication preferences, many victim service programs are expanding their traditional telephone hotlines and adding web chat or text hotlines. However, there is little research available about these web and text-based hotlines. We examined program data collected in the first year of operation of a web-based crisis hotline for sexual assault survivors at a large Midwestern university in the United States as part of a larger evaluation project. We examined how often the web-based chat hotline was used and explored patterns of use by time of day and month, comparing to records from the phone hotline operated by the same campus-based victim service program. We also conducted interviews and two group discussions with volunteers and staff about their experiences with providing crisis intervention in a web-chat medium. Findings suggest that the web-based crisis hotline is being used frequently, nearly as often as the telephone hotline and doubling the total number of crisis contacts the organization had in the year prior to adding the web-based chat hotline. Staff and volunteers identified a number of advantages of a web-based hotline, including increased privacy and accessibility for survivors. Difficulty identifying and conveying emotions in the web-chat context was one of the primary challenges described by staff and volunteers. Operating the web-hotline, therefore, requires additional training for volunteers and staff on how to translate crisis intervention skills into a text-based medium. Suggestions for how to communicate effectively in text-based crisis intervention are discussed, along with other considerations for designing a web or text hotline.